Goethe's Faust and the Divan of Ḥāfiẓ Body and Soul in Pursuit of Knowledge and Beauty - Michaeli, Hiwa (De Gruyter, 2019)
This book explores the poetic articulations of a shift from a transcendent to an immanent worldview, as reflected in the manner of evaluation of body and soul in Goethe's Faust and Ḥāfiẓ' Divan. Focusing on two lifeworks that illustrate their authors' respective intellectual histories, this cross-genre study goes beyond the textual confines of the two poets' Divans to compare their intellectual worlds.